THE CORRELATION BETWEEN BREAKFAST HABITS WITH LEARNING ACHIEVEMENT IN STUDENT AT STIKES DUTA GAMA KLATEN - Happy Primariasari (STIKES DUTAGAMA KLATEN, 2021)
Background: breakfast habits are very important for the students to maintain health. Breakfast for students can improve concentration and understanding the lesson so it may improve students’ achievement as well. Based on an observational study, it was shown that 46% of students did not have breakfast habit. In addition, 46,67% of the students had a good academic achievement, 36,67% of the students had avarage academic achievement, while 16,67% of the students had poor academic achievement. This study aims to determain the correlation between breakfast habits with learning achievement in student at Stikes Duta Gama Klaten. Method: This study uses an analytic observational method with a cross sectional approach. This study was conducted at Stikes Duta Gama Klaten.. The study population was all students at Stikes Duta gama Klaten with total sample of 30 respondent using probability sampling technique. Research variables included breakfast habits and learning achievement. Data on breakfast habits using questionnaires and learning achievement of report book (Kartu Hasil Studi). Statistical test using Statistical test of the research was Chi-Square. Result: this study showed that most of respondent did not have breakfast habit (6,67%). The correlation between breakfast habit and academic achievement was p: 0,03 >0,05. conclusion: There were correlations between breakfast habits with learning achievement in student at Stikes Duta Gama Klaten.